ANALISIS YURIDIS CALON TUNGGAL DALAM PEMILIHAN KEPALA DAERAH DI INDONESIA (Studi Putusan Mahkamah Konstitusi Nomor 100/PUU-XIII/2015 Tentang Pengujian Undang-Undang Nomor 8 Tahun 2015 Tentang Perubahan Atas Undang-Undang Nomor 1 Tahun 2015 Tentang Penetapan Peraturan Pemerintah Pengganti Undang-Undang Nomor 1 Tahun 2014 Tentang Pemilihan Gubernur, Bupati, dan Walikota menjadi Undang-Undang) - Syahrudin, Riko; Indra, Mexsasai; ', Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Election is an important instrument to embody the sovereignty of the people, filling the post of head of local elected democratically. Elections under Act Number 8 of 2015 held simultaneously, up to the national elections simultaneously, 2027. The implementation of simultaneous elections in 2015 beginning with the registration of candidates, led to the phenomenon of a single pair of candidates in three regions. Do Effendi Gazali judicial review by the Constitutional Court, the Court granted to most of the Decision Number 100/PUU-XIII/2015. The elections with a single candidate remains to be implemented with the system plebiscite of the people choose to agree and disagree, in consideration of saving people's right to elect and be elected. This type of research can be classified in normative law research that is legal literature. In this normative legal study authors conducted a study of the principles of law. The data source is equipped with primary data, secondary data and data tertiary, and processed by qualitative analysis method deductively.From the research problem there are two main things that can be inferred. First, consideration of the Constitutional Court in order to ensure the fulfillment of citizens' constitutional rights, implementation of the people's sovereignty, the right to choose and pick, local elections should go ahead even though there is one candidate, which has been cultivated in earnest to get at least two pairs of candidates. In the system of filling the positions of election , the elections without electoral contestation is essentially not in the same breath with the principle of Luber and Jurdil. Second, the legal implications arising related to the Constitutional Court decision, namely, the birth PKPU Number 14 of 2015, and PMK Number 4 of 2015. Advice writer, first, to maximize the function of political recruitment owned by political parties and independent candidates to participate in local elections, Second, the revision of the Law on local elections should accommodate the new provisions in the event of a single candidate pair.Key Words: Single Candidate - Election - Constitutional Court Decision